Learning Virtual Communities: Emerging environments for the development of digital competences in times of COVID-19 - Cordero, Jessica Alejandra; Rodríguez González, Josefina (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The social and educational isolation lived around the world due to SARS-CoV2 has put upon challenges for teachers, students and parents. They have managed to use technological tools to do homework and attend communication assignments. Social networks have worked as a means of communication thus creating virtual learning communities for whoever has academical and technological doubts, as well as emotional support. Therefore, in this document participants will be analyzed along with their interactions and resources used to reinforce their digital competences. This will be done through the study of a virtual group called “Aprende en Casa 6° de Primaria”.